Traditional Chinese Medicine Tang-Luo-Ning Ameliorates Sciatic Nerve Injuries in Streptozotocin-Induced Diabetic Rats - Zou, Da-Wei (Hindawi Publishing Corporation, 2013)
Diabetic peripheral neuropathy (DPN) is a common microvascular complication of diabetes associated with high disability rate and low quality of life. Tang-Luo-Ning (TLN) is an effective traditional Chinese medicine for the treatment of DPN. To illustrate the underlying neural protection mechanisms of TLN, the effect of TLN on electrophysiology and sciatic nerve morphology was investigated in a model of streptozotocin-induced DPN, as well as the underlying mechanism. Sciatic motor nerve conduction velocity and digital sensory nerve conduction velocity were reduced in DPN and were significantly improved by TLN or α-lipoic acid at 10 and 20 weeks after streptozotocin injection. It was demonstrated that TLN intervention for 20 weeks significantly alleviated pathological injury as well as increased the phosphorylation of ErbB2, Erk, Bad (Ser112), and the mRNA expression of neuregulin 1 (Nrg1), GRB2-associated binding protein 1 (Gab1), and mammalian target of rapamycin (Mtor) in injured sciatic nerve. These novel therapeutic properties of TLN to promote Schwann cell survival may offer a promising alternative medicine for the patients to delay the progression of DPN. The underlying mechanism may be that TLN exerts neural protection effect after sciatic nerve injury through Nrg1/ErbB2→Erk/Bad Schwann cell survival signaling pathway.